Fatores de risco para leishmaniose visceral em Belo Horizonte, Minas Gerais, 2006 - Barbara Kellen Antunes Borges (2006)
The present study was conducted in order to analyze the possible risk factors involved the occurrence of Visceral Leishmaniasis (VL) in Belo Horizonte/MG, in 2006. It was made a case-Control study using questionnaire, images registration inside and outside of the affected dwellings and collection of canine blood. The sample was constituted by 82 human cases of VL occurred in 2004 and 164 controls (neighbors of the left and of the right of the cases). The nine regional administrative branch of the Town Hall of Belo Horizonte participated with residences in the study, in spite of not have aimed at geographical level of the disease. The collection of data of the cases happened with the relatives' participation, when it was not possible to do with the own cases. The biological material sample was sent to the laboratory of Leishmaniasis of the Veterinary School of UFMG for accomplishment of laboratory analysis (ELISA and IFAT). The interviewed population was characterized for being adult, with feminine sex slightly predominant. Larger occurrence of VL was noticed among children with age less or equal to 10 years. In relation to the dwellings, the risk factors show significant effect were: if there is a hen house in the propriety, humidity, garbage, fallow lands, If there is fruit or vegetable crop in the house, besides the presence of others animals such as rodents, birds and cats. Due to the low index of canine seropositivity, the dog presence in the residence was considered without statistical effect, which can be inferred a effective control of the animals soropositive for VL in areas with occurrence of human cases. The orientation of the people about the main VL information showed a potential protection, being estimated 2,24 times less likely of have a diseased among the people that have any knowledge about VL.